2000
DOI: 10.1002/hep.510310133
|View full text |Cite
|
Sign up to set email alerts
|

Natural fluctuations of hepatitis C viral load in a homogeneous patient population: A prospective study

Abstract: Hepatitis C virus (HCV) infection is the main cause of parenteral non-A, non-B hepatitis. 1-5 HCV consists of a heterogeneous mix of isolates defined by genotype, each of which is further classified into subtypes. A number of factors have been identified as important in predicting the outcome of disease progression. These include age at infection, viral type/subtype, viral load, quasispecies, and mode of infection. [6][7][8][9][10] Clinical heterogeneity in disease progression may reflect either viral heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Imprecision may have been relatively high (due to the use of several testing laboratories, technologists, runs, and reagent lots), but the same well-characterized HCV RNA assay was used for all six trials. If these trials' HCV RNA testing yielded within-patient variability of approximately Ϯ0.5 log 10 IU/ml, as others have reported (1,9,12,18,22,34,39,44,49,63), such "noise" in single [HCV RNA] values would not have affected our analyses more they did than in earlier studies. (21).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Imprecision may have been relatively high (due to the use of several testing laboratories, technologists, runs, and reagent lots), but the same well-characterized HCV RNA assay was used for all six trials. If these trials' HCV RNA testing yielded within-patient variability of approximately Ϯ0.5 log 10 IU/ml, as others have reported (1,9,12,18,22,34,39,44,49,63), such "noise" in single [HCV RNA] values would not have affected our analyses more they did than in earlier studies. (21).…”
Section: Discussionmentioning
confidence: 74%
“…We therefore analyzed the baseline characteristics of 2,472 HCV genotype 1-infected patients to identify correlations with gender, age, race, weight, body mass index (BMI), HCV acquisition mode, HCV subtype, alanine aminotransferase concentration, or histopathologic changes in the liver. After separation of the data according to four [HCV RNA] BL groups (<5.0, >5.0 to 5.6, >5.6 to 5.9, and >5.9 log 10 IU/ml), we determined that increasing The serum levels of hepatitis C virus (HCV) RNA represent the abundance of HCV production versus clearance and are usually stable in humans with untreated chronic hepatitis C (CHC) (1,9,12,18,22,34,39,44,49,63). Between individuals, however, these baseline HCV RNA concentrations ([HCV RNA] BL ) vary by 3 to 4 log 10 IU/ml and the factors that determine these differences are poorly understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturer has shown that the second-generation tests can detect 100% of samples containing as little as 50 IU/ml (approximately 100 copies/ml) (13). Although the fluctuations in viral load that occur in patients chronically infected with HCV are not well defined, it is rare to find patients with viral loads of Ͻ10 4 copies/ml in the absence of therapy (8,12,14,15,(17)(18)(19)(20). Thus, it appears that the analytical sensitivity of the AMPLICOR tests is at least 100-fold lower than the lowest value likely to be encountered in patients being evaluated for HCV infection prior to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Interperson variability in viraemia was investigated in the HAD-1b group of 47 patients (58). None of the patients included in the study had received anti-viral therapy.…”
Section: Clinicopathology and Virology Of Had-1b Infected Individualsmentioning
confidence: 99%